A novel MT-CO2 m.8249G > A pathogenic variation and the MT-TW m.5521G > A mutation in patients with mitochondrial myopathy. (October 2014) - Mkaouar-Rebai, Emna; Ben Mahmoud, Afif; Chamkha, Imen; Chabchoub, Imen; Kammoun, Thouraya; Hachicha, Mongia; Fakhfakh, Faiza
Abstract Mitochondrial DNA (mtDNA) defects were known to be associated with a large spectrum of human diseases and patients might present wide range of clinical features with various combinations. Mutations in mitochondrial tRNAs, rRNAs and protein-coding genes or large-scale rearrangements have been implicated in several cytopathies. Mitochondrial myopathies, usually maternally inherited group of neuromuscular diseases caused by mitochondrial dysfunction occurring before the age of 20 years and often begin with exercise intolerance, muscle weakness and neurodevelopmental retardation. We studied the mtDNA in three Tunisian patients with mitochondrial myopathy. The mutational analysis screening revealed the presence of two mitochondrial mutations: the m.5521G > A mutation in the D-stem region of the tRNATrp gene which could lead to a disruption of the secondary structure of this tRNA and affect the tRNA–ribosome interaction with a consequent decrease in the rate of synthesis of mitochondrial proteins. The second mutation is the m.8249G > A (p.G222R) variation in the MT-CO2 gene which may affect the electrons transfer from cytochrome c to the bimetallic center of the catalytic subunit I.